Studies on Removal of Cr (VI) from Aqueous Solutions Using Powder of Mosambi Fruit Peelings (PMFP) As a Low Cost Sorbent - R. Hema Krishna; A. V. V. S. Swamy (E-Journal of Chemistry)
The powder of mosambi fruit peelings (PMFP) was used as an adsorbent for the removal of heavy metal like Cr (VI) from aqueous solutions was studied using batch tests. The influence of physico-chemical key parameters such as the initial metal ion concentration, pH, agitation time, adsorbent dosage, and the particle size of adsorbent has been considered in batch tests. Sorbent ability to adsorb Cr (VI) ions was examined and the mechanism involved in the process investigated. The optimum results were determined at an initial metal ion concentration was 10 mg/lit, pH=2, agitation time – 60 min, an adsorbent dose (150 mg/50 ml) and the particle size (0.6 mm). The % adsorption, Langmuir constants [Q0=7.51(mg/g) and b=1.69(mg/lit)] Freundlich constant(Kf=2.94), Lagergren rate constants (Kad (min-1)=5.75 x 10-2) for [Cr(VI)] 10 mg/lit were determined for the adsorption system as a function of sorbate concentration. The equilibrium data obtained were tested using Langmuir, Freundlich adsorption isotherm models, and the kinetic data obtained were fitted to pseudo first order model.